Pulmonary hemodynamic responses to in utero ventilation in very immature fetal sheep - Allison Beth J; Crossley Kelly J; Flecknoe Sharon J; Morley Colin J; Polglase Graeme R; Hooper Stuart B (Respiratory Research, 2010)
Abstract Background The onset of ventilation at birth decreases pulmonary vascular resistance (PVR) resulting in a large increase in pulmonary blood flow (PBF). As the large cross sectional area of the pulmonary vascular bed develops late in gestation, we have investigated whether the ventilation-induced increase in PBF is reduced in immature lungs. Methods Surgery was performed in fetal sheep at 105 d GA (n = 7; term ~147 d) to insert an endotracheal tube, which was connected to a neonatal ventilation circuit, and a transonic flow probe was placed around the left pulmonary artery. At 110 d GA, fetuses (n = 7) were ventilated in utero (IUV) for 12 hrs while continuous measurements of PBF were made, fetuses were allowed to develop in utero for a further 7 days following ventilation. Results PBF changes were highly variable between animals, increasing from 12.2 ± 6.6 mL/min to a maximum of 78.1 ± 23.1 mL/min in four fetuses after 10 minutes of ventilation. In the remaining three fetuses, little change in PBF was measured in response to IUV. The increases in PBF measured in responding fetuses were not sustained throughout the ventilation period and by 2 hrs of IUV had returned to pre-IUV control values. Discussion and conclusion Ventilation of very immature fetal sheep in utero increased PBF in 57% of fetuses but this increase was not sustained for more than 2 hrs, despite continuing ventilation. Immature lungs can increase PBF during ventilation, however, the present studies show these changes are transient and highly variable.